A Caribbean evaluation of public versus private drinking water provision: the case of St. Maarten, Netherlands Antilles. (15th July 2008) - Schouten, Marco A.C.; Brdjanovic, Damir; Van Dijk, Meine Pieter
This article assesses how a small island state can choose the best option in the process of private sector involvement. It reviews the decision process to involve or not the private sector in water and sanitation supply and in which way. Nine criteria are used to make the choice. A careful weighing process is necessary, taking the history into account, looking at the special institutional situation in the country and involving the stakeholders, and even then there is no guarantee of success! An existing public utility may be better placed to look after the modernisation and extension of the water and sanitation system than a new private firm.